2023
DOI: 10.1136/gutjnl-2022-327448
|View full text |Cite
|
Sign up to set email alerts
|

Activated regulatory T-cells promote duodenal bacterial translocation into necrotic areas in severe acute pancreatitis

Abstract: ObjectiveIn acute pancreatitis (AP), bacterial translocation and subsequent infection of pancreatic necrosis are the main risk factors for severe disease and late death. Understanding how immunological host defence mechanisms fail to protect the intestinal barrier is of great importance in reducing the mortality risk of the disease. Here, we studied the role of the Treg/Th17 balance for maintaining the intestinal barrier function in a mouse model of severe AP.DesignAP was induced by partial duct ligation in C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…Intriguingly, most of the GFP-marked bacteria were observed in the pancreatic duct or out of the pancreatic parenchyma in the 9 h group (9H) and they were dispersed in pancreatic parenchyma in 21 h group (21H), accompanied by the significant upregulated level of Treg and PD-1 positive Treg (Figure 2B,C). Combined with the potential function of Treg reported by Glaubitz et al, 6 we hypothesized pancreatic PD-1 expression and Treg facilitate the translocation of commensal bacteria into pancreatic necrosis. Then, we used PD-1 antibody on a mouse model after 12 h to detect whether PD-1 blockage therapy could reverse the bacteria translocation.…”
Section: E T T E R T O T H E J O U R N a L Ctm2-2023-06-1111: Targeti...mentioning
confidence: 58%
See 3 more Smart Citations
“…Intriguingly, most of the GFP-marked bacteria were observed in the pancreatic duct or out of the pancreatic parenchyma in the 9 h group (9H) and they were dispersed in pancreatic parenchyma in 21 h group (21H), accompanied by the significant upregulated level of Treg and PD-1 positive Treg (Figure 2B,C). Combined with the potential function of Treg reported by Glaubitz et al, 6 we hypothesized pancreatic PD-1 expression and Treg facilitate the translocation of commensal bacteria into pancreatic necrosis. Then, we used PD-1 antibody on a mouse model after 12 h to detect whether PD-1 blockage therapy could reverse the bacteria translocation.…”
Section: E T T E R T O T H E J O U R N a L Ctm2-2023-06-1111: Targeti...mentioning
confidence: 58%
“…The depletion of Tregs could decrease the bacterial translocation into pancreatic necrosis and targeting Tregs in acute pancreatitis (AP) may help to ameliorate the disease course. 1 Here, we would like to highlight the important role of Programmed-death 1+ (PD-1+) pancreatic Tregs in infectious pancreatic necrosis after acute pancreatitis and propose a new potential therapeutic method through PD-1 blockage.…”
Section: E T T E R T O T H E J O U R N a L Ctm2-2023-06-1111: Targeti...mentioning
confidence: 99%
See 2 more Smart Citations
“…The uncontrolled activation of inflammatory signals and the intense release of inflammatory cytokines resulted in the severity of the patients 15 . Researchers have found that inflammation can spread from the local pancreas to nearby tissues, or cause systemic inflammation through the cascade activation of cytokines 16–18 . In this context, We retrospectively analyzed the data of 12 serum cytokines at admission of 307 patients with AP, and further evaluated their relationship with AP severity and early complications.…”
Section: Introductionmentioning
confidence: 99%